PENGEMBANGAN MODUL PRAKTIKUM KIMIA BERBASIS PROBLEM BASED LEARNING (PBL) PADA POKOK BAHASAN ASAM BASA UNTUK KELAS XI TINGKAT SMA/MA SEDERAJAT - Rahmad Zuhri; Maria Erna; Elva Yasmi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: Research development of chemical- learning media module of practical based Problem Based Learning (PBL) was intended to produce a valid practical module acid base by aspects of content, graphics, presentations, and languange. Other than that for know respons teacher and students to learning media of practical module acid base was developed. Research development of media used ADD models haven 3 steps was Analysis, Design, and Development. Result of research development of acid base practical module based Problem Based Learning (PBL) was valids by 3 validator’s people and otherwise valid of aspect contents, languanges, presentations, and graphics with an average percentage of 88.47% (category valid). Response was rated by 18 respondens in SMAN 5 and MAN 1 Pekanbaru and declared percentage respons of 87,48% (category strongly agree). This indicates that the learning media in the form of acid-base experiment module based on Problem Based Learning (PBL) declared valid.